Magnesium-titanium-aluminum doped sodium vanadium phosphate as well as preparation method and application thereof

By introducing multiple elements such as magnesium, titanium and aluminum into sodium vanadium phosphate, magnesium, titanium and aluminum doped with sodium vanadium phosphate, the problems of low energy density and poor rate performance of vanadium phosphate are solved, and higher energy density and rate performance are achieved, while maintaining structural stability and safety.

CN119841296APending Publication Date: 2025-04-18DALIAN RONGKE ENERGY STORAGE GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411955671.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-28
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The low energy density and poor rate performance of existing sodium vanadium phosphate limit its application in electric vehicles and energy storage systems.

Method used

By introducing multiple elements such as magnesium, titanium and aluminum, magnesium-titanium-aluminum doped with vanadium phosphate, synergistic modification optimizes its electrochemical performance.

Benefits of technology

It significantly improves the energy density and rate performance of sodium vanadium phosphate, while maintaining structural stability and safety, meeting a wider application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841296A_ABST
    Figure CN119841296A_ABST
Patent Text Reader

Abstract

The invention provides magnesium-titanium-aluminum doped sodium vanadium phosphate and a preparation method and application thereof.The preparation method of the magnesium-titanium-aluminum doped sodium vanadium phosphate comprises the following steps that a vanadium source, a phosphorus source, a sodium source, a magnesium source, a titanium source and an aluminum source are weighed according to the element ratio and mixed in deionized water, a reducing agent is added, and a mixed solution is obtained; performing pretreatment on the mixed solution by adopting spray drying to prepare a precursor; putting the precursor into a high-temperature furnace, presintering for 2-4 hours at 350-500 DEG C in an inert atmosphere, and then calcining for 6-12 hours at 800-950 DEG C; and after calcining, grinding and screening to prepare the magnesium-titanium-aluminum doped sodium vanadium phosphate. According to the invention, magnesium, titanium and aluminum elements are introduced into the lattice structure of sodium vanadium phosphate to form the composite material with excellent electrochemical performance. The magnesium-titanium-aluminum doped sodium vanadium phosphate not only inherits the original stability advantage of sodium vanadium phosphate, but also is remarkably improved in the aspects of energy density, rate capability, cycling stability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to sodium vanadium phosphate technology, and in particular to magnesium-titanium-aluminum doped sodium vanadium phosphate, and a preparation method and application thereof. Background Art

[0002] With the transformation of the global energy structure and the rapid development of emerging industries such as electric vehicles and large-scale energy storage systems, the demand for high-performance energy storage materials is becoming increasingly urgent. Sodium vanadium phosphate (NVP), as a potential cathode material for sodium-ion batteries, has attracted widespread attention due to its structural stability and safety. However, its low energy density and rate performance limit its commercial application. In the traditional synthesis of sodium vanadium phosphate, single elements are often used for doping synthesis, such as Mg, Ti, Nb, etc., but they are often limited by the limitations of a single coating, such as the increase of side reactions during the cycle, the difficulty in achieving expected structural stability, and the overgrowth of unit cells due to coating. Therefore, on the basis of a single coating, we will consider the synergistic effect between doping elements, further optimize the doping effect, and improve the practicability of sodium vanadium phosphate. Summary of the invention

[0003] The purpose of the present invention is to propose a magnesium-titanium-aluminum-doped sodium vanadium phosphate to address the problems of low energy density and poor rate performance of the existing sodium vanadium phosphate, introduce multiple elements of magnesium (Mg), titanium (Ti) and aluminum (Al) into the lattice structure of the sodium vanadium phosphate, and synergistically modify and optimize the sodium vanadium phosphate to improve its electrochemical properties, especially energy density and rate performance, while maintaining its structural stability and safety to meet a wider range of application needs.

[0004] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising", etc. and similar meanings, as well as closed-ended "composed of", "composed of", etc. and similar meanings.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is: a magnesium-titanium-aluminum doped sodium vanadium phosphate, the general formula of which is Na 3 V 2-x Mg x / 4 Ti x / 4 Al x / 2 (PO 4 ) 3 , where 0.1≤x≤0.5.

[0006] Furthermore, the doping amount of magnesium, titanium and aluminum does not exceed 10% of the total molar amount of metal ions, preferably 2-4%.

[0007] Furthermore, the particle size of the magnesium-titanium-aluminum-doped sodium vanadium phosphate is: 0.8 μm≤D50≤10 μm.

[0008] Another object of the present invention is to disclose a method for preparing magnesium-titanium-aluminum-doped sodium vanadium phosphate, comprising the following steps:

[0009] Step 1: Mix the raw materials

[0010] According to the element ratio in the general formula, a vanadium source, a phosphorus source, a sodium source, a magnesium source, a titanium source and an aluminum source are weighed respectively, mixed in deionized water, and a reducing agent is added to obtain a mixed solution;

[0011] Step 2: Precursor preparation

[0012] The mixed solution is pre-treated by spray drying to prepare a precursor;

[0013] Step 3: Calcination

[0014] The precursor is placed in a high-temperature furnace and calcined under the protection of an inert atmosphere. The calcination causes a chemical reaction between the raw materials to form a stable sodium vanadium phosphate-based composite material; first pre-sintering at 350-500°C for 2-4h to ensure the reduction reaction during the calcination process, and then calcining at 800-950°C for 6-12h;

[0015] Step 4: Post-processing

[0016] After calcination, the magnesium-titanium-aluminum doped sodium vanadium phosphate is prepared by grinding and screening.

[0017] Furthermore, the element ratio in step 1 is V:P:Na:Mg:Ti:Al=2-x:3:3:x / 4:x / 4:x / 2, wherein the value range of x is 0.1≤x≤0.5.

[0018] Furthermore, the vanadium source in step 1 is vanadium pentoxide V 2 O 5 NH 4 VO 3 、V 2 O 4 、V 2 O 3 and (NH4) 2 V 6 O 16 One or more of, preferably vanadium pentoxide V 2 O 5 .

[0019] Furthermore, the phosphorus source in step 1 is diammonium phosphate NH 4 H 2 PO 4 , H 3 PO 4 , P 2 O 5NH 4 ) 3 PO 4 and NH 4 VPO 4 One or more of, preferably diammonium phosphate NH 4 H 2 PO 4 .

[0020] Furthermore, the sodium source in step 1 is sodium carbonate Na 2 CO 3 , NaCl, NaOH and NaHCO 3 One or more of, preferably sodium carbonate Na 2 CO 3 .

[0021] Furthermore, the magnesium source in step 1 is magnesium oxide MgO, Mg(OH) 2 MgCO 3 and Mg(NO 3 ) 2 One or more of, preferably magnesium oxide MgO.

[0022] Furthermore, the titanium source in step 1 is titanium dioxide TiO 2 、TiCl 4 and H 2 TiO 3 One or more of, preferably titanium dioxide TiO 2 .

[0023] Furthermore, the aluminum source in step 1 is aluminum oxide Al 2 O 3 、Al(OH) 3 、AlCl 3 and Al(NO 3 ) 3 One or more of, preferably aluminum oxide Al 2 O 3 .

[0024] Furthermore, the solid content of the mixed solution in step 1 is 35-55%. Unless otherwise specified, % in the present invention refers to mass percentage.

[0025] Furthermore, the reducing agent in step 1 is one or more of citric acid and ascorbic acid.

[0026] Furthermore, the amount of the reducing agent added in step 1 is 5wt%-12wt%, preferably 6wt%-10wt%.

[0027] The addition of the reducing agent of the present invention can not only play a reducing role in the solution, inhibit the oxidation of the vanadium source, and promote the reduction of the vanadium source, but also play a role as a complexing agent, accelerate the synthesis of the precursor in the solution, and promote the reaction in the solution.

[0028] Furthermore, the spray drying conditions in step 2 are: spray inlet temperature 180°C-220°C, outlet temperature 80°C-120°C, flow rate 20-40rpm, pressure 0.2-0.5Mpa.

[0029] Furthermore, the inert atmosphere in step 3 is one or more of nitrogen and argon. The inert atmosphere can prevent the material from being oxidized at high temperature and ensure the smooth progress of the synthesis process.

[0030] Furthermore, the calcination conditions in step 3 are preferably: pre-sintering at 400-500°C for 3-4h, and then calcining at 800-850°C for 8-12h. Reasonable calcination conditions can control the crystallinity and phase purity of the material, which has an important influence on the structure and performance of the material.

[0031] Furthermore, the screening in step 4 uses a 300-mesh sieve.

[0032] Another object of the present invention is to disclose an application of magnesium-titanium-aluminum doped sodium vanadium phosphate in the field of positive electrode materials for sodium ion batteries.

[0033] The magnesium-titanium-aluminum doped sodium vanadium phosphate, its preparation method and application have the following advantages compared with the prior art:

[0034] The present invention precisely controls the raw material ratio and synthesis process conditions to dope magnesium, titanium and aluminum into the lattice structure of sodium vanadium phosphate in situ, thereby forming a composite material with excellent electrochemical properties. The composite material not only inherits the original stability advantage of sodium vanadium phosphate, but also has significant improvements in energy density, rate performance and cycle stability.

[0035] Mg doping can change the crystal structure and electronic properties of the positive electrode material to form a more stable structure. This structural change helps to reduce the volume change of the material during the charge and discharge process and improve the structural stability of the material. When doping the transition metal site located on the surface of the crystal structure, Mg doping can also inhibit adverse side reactions and structural phase changes in the positive electrode material. These side reactions and phase changes usually lead to the degradation of material performance and shortened battery life. The addition of Mg can inhibit the occurrence of these harmful processes by changing the microstructure and electronic properties of the material.

[0036] Ti doping can optimize the microstructure of the positive electrode material, making the diffusion of sodium ions in the material smoother, thereby improving the rate performance of the battery. Similarly, Ti doping helps to inhibit the structural degradation and side reactions of the positive electrode material during the charge and discharge process, thereby improving the cycle stability of the battery. Al doping can introduce defects or new electronic states into the positive electrode material, improve the electronic conductivity of the material, help improve the rate performance of the battery, and enable the battery to charge and discharge faster. When Al is co-doped with other elements (such as Ti), a synergistic effect can be produced to further improve the performance of the positive electrode material.

[0037] The synergistic effect brought by aluminum doping is optimized by adding Mg and Ti elements. The addition of Mg source increases the transmission distance of sodium ions, and the Ti source is doped with Mg and Al to optimize the structural stability on the basis of internal vacancy defects. The Al source is conducive to further optimizing the rate and cycle performance of the material, and the NVP constructed by the synergistic effect of multi-element doping has further application value. The present invention optimizes the crystal structure through the synergistic effect between multiple elements, maintains the stability of the crystal structure, and improves the intrinsic conductivity of the material, and improves the charge and discharge performance of the material.

[0038] In summary, the magnesium-titanium-aluminum doped sodium vanadium phosphate of the present invention has the advantages of high energy density and good rate performance while maintaining the original structural stability and safety of sodium vanadium phosphate, and can meet the needs of high-performance energy storage. It has good application prospects and large-scale promotion potential in the fields of electric vehicles, energy storage grids, and portable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the XRD spectrum of magnesium titanium aluminum doped sodium vanadium phosphate in Example 1.

[0040] Figure 2 This is a scanning electron microscope (SEM) image 1 of magnesium-titanium-aluminum-doped sodium vanadium phosphate in Example 1.

[0041] Figure 3 This is the second scanning electron microscope (SEM) image of magnesium titanium aluminum doped sodium vanadium phosphate in Example 1. DETAILED DESCRIPTION

[0042] The present invention is further described below with reference to the examples. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0043] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0044] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0045] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0046] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0047] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0048] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.

[0049] In this manual, the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0050] Unless otherwise specified, % in this specification refers to mass percentage.

[0051] Example 1

[0052] This embodiment discloses a magnesium-titanium-aluminum doped sodium vanadium phosphate, and the preparation method thereof is as follows:

[0053] Step 1, raw material mixing: molar ratio V:P:Na:Mg:Ti:Al = 1.94:3:3:0.015:0.015:0.03, weigh vanadium pentoxide V 2 O 5 、Ammonium dihydrogen phosphate NH 4 H 2 PO 4 、Sodium carbonate Na 2 CO 3 , magnesium oxide MgO, titanium dioxide TiO 2 and alumina Al 2 O 3 As raw materials, the raw materials were mixed in deionized water (solid content 40 wt%), 8 wt % of citric acid was added as a reducing agent, and stirred uniformly at 80°C.

[0054] Step 2, precursor preparation: The solution is then spray dried with an inlet temperature of 200° C., an outlet temperature of 80° C., a flow rate of 20 rpm, and a pressure of 0.3 MPa to form a precursor of sodium vanadium phosphate.

[0055] Step 3, calcination treatment: Place the precursor powder in a muffle furnace, and under nitrogen protection, heat it to 450°C at a rate of 5°C / min, and keep this temperature for 4 hours to ensure that the precursor is fully reduced, and then heat it to 800°C at 5°C / min and keep it for 12 hours to ensure that the raw materials are fully reacted and form a stable sodium vanadium phosphate-based composite material.

[0056] Step 4, post-treatment: the calcined product is naturally cooled to room temperature, and then ground and sieved through a 300-mesh sieve to obtain magnesium-titanium-aluminum-doped sodium vanadium phosphate with uniform particle size.

[0057] Example 2

[0058] This embodiment discloses a magnesium-titanium-aluminum doped sodium vanadium phosphate, and the preparation method thereof is as follows:

[0059] Step 1, raw material mixing: according to the molar ratio of V:P:Na:Mg:Ti:Al=1.9:3:3:0.025:0.025:0.05, weigh vanadium pentoxide V 2 O 5 、Ammonium dihydrogen phosphate NH 4 H 2 PO 4 、Sodium carbonate Na 2 CO 3 , magnesium oxide MgO, titanium dioxide TiO 2 and alumina Al 2 O 3 As raw materials, the raw materials were mixed in deionized water (solid content 40 wt%), 8 wt % of citric acid was added as a reducing agent, and stirred uniformly at 80°C.

[0060] Step 2, precursor preparation: The solution is then spray dried with an inlet temperature of 200° C., an outlet temperature of 80° C., a flow rate of 20 rpm, and a pressure of 0.3 MPa to form a precursor of sodium vanadium phosphate.

[0061] Step 3, calcination treatment: Place the precursor powder in a muffle furnace, and under nitrogen protection, heat it to 450°C at a rate of 5°C / min, and keep this temperature for 4 hours to ensure that the precursor is fully reduced, and then heat it to 800°C at 5°C / min and keep it for 12 hours to ensure that the raw materials are fully reacted and form a stable sodium vanadium phosphate-based composite material.

[0062] Step 4, post-treatment: the calcined product is naturally cooled to room temperature, and then ground and sieved through a 300-mesh sieve to obtain magnesium-titanium-aluminum-doped sodium vanadium phosphate with uniform particle size.

[0063] Example 3

[0064] This embodiment discloses a magnesium-titanium-aluminum doped sodium vanadium phosphate, and the preparation method thereof is as follows:

[0065] Step 1, raw material mixing: according to the molar ratio of V:P:Na:Mg:Ti:Al=1.88:3:3:0.03:0.03:0.06, weigh vanadium pentoxide V 2 O 5 、Ammonium dihydrogen phosphate NH 4 H 2 PO 4 、Sodium carbonate Na 2 CO 3 , magnesium oxide MgO, titanium dioxide TiO 2 and alumina Al 2 O 3 As raw materials, the raw materials were mixed in deionized water (solid content 40 wt%), 8 wt % of citric acid was added as a reducing agent, and stirred uniformly at 80°C.

[0066] Step 2, precursor preparation: The solution is then spray dried with an inlet temperature of 200° C., an outlet temperature of 80° C., a flow rate of 20 rpm, and a pressure of 0.3 MPa to form a precursor of sodium vanadium phosphate.

[0067] Step 3, calcination treatment: Place the precursor powder in a muffle furnace, and under nitrogen protection, heat it to 450°C at a rate of 5°C / min, and keep this temperature for 4 hours to ensure that the precursor is fully reduced, and then heat it to 800°C at 5°C / min and keep it for 12 hours to ensure that the raw materials are fully reacted and form a stable sodium vanadium phosphate-based composite material.

[0068] Step 4, post-treatment: the calcined product is naturally cooled to room temperature, and then ground and sieved through a 300-mesh sieve to obtain magnesium-titanium-aluminum-doped sodium vanadium phosphate with uniform particle size.

[0069] Comparative Example 1

[0070] This comparative example discloses a sodium vanadium phosphate, the preparation method of which is as follows:

[0071] Raw material ratio: according to the molar ratio of V:P:Na=2:3:3, weigh vanadium pentoxide V 2 O 5 、Ammonium dihydrogen phosphate NH 4 H 2 PO 4 、Sodium carbonate (Na 2 CO 3 As raw material.

[0072] Precursor preparation: The weighed raw materials were mixed in deionized water, 8 wt% of citric acid was added as a reducing agent, and stirred at 80°C. The sol was then spray dried at an inlet temperature of 200°C, an outlet temperature of 80°C, a flow rate of 20 rpm, and a pressure of 0.3 MPa to form a precursor of sodium vanadium phosphate.

[0073] Calcination treatment: The precursor powder is placed in a muffle furnace, and under nitrogen protection, the temperature is raised to 450°C at a rate of 5°C / min, and the temperature is maintained for 4 hours to ensure that the precursor is fully reduced, and then the temperature is raised to 800°C at a rate of 5°C / min and maintained for 12 hours to ensure that the raw materials are fully reacted and form a stable sodium vanadium phosphate-based composite material.

[0074] Post-treatment: The calcined product is naturally cooled to room temperature, and then ground and sieved through a 300-mesh sieve to obtain a magnesium-titanium-aluminum multi-element doped sodium vanadium phosphate material with uniform particle size.

[0075] Comparative Example 2 (Single Element Doping Experiment)

[0076] This comparative example discloses a magnesium-doped sodium vanadium phosphate, the preparation method of which is as follows:

[0077] Step 1, raw material mixing: according to the molar ratio of V:P:Na:Mg=1.9:3:3:0.1, weigh vanadium pentoxide V 2 O 5 、Ammonium dihydrogen phosphate NH 4 H 2 PO 4 、Sodium carbonate Na 2 CO 3 、MgO / TiO 2 / AluminaAl 2 O 3 The raw materials were mixed in deionized water, 8 wt % of citric acid was added as a reducing agent, and the mixture was stirred at 80° C. to be uniform.

[0078] Step 2, precursor preparation: The solution is then spray-dried with an inlet temperature of 200° C., an outlet temperature of 80° C., a flow rate of 20 rpm, and a pressure of 0.3 MPa to form a precursor of sodium vanadium phosphate.

[0079] Step 3, calcination treatment: Place the precursor powder in a muffle furnace, and under nitrogen protection, heat it to 450°C at a rate of 5°C / min, and keep this temperature for 4 hours to ensure that the precursor is fully reduced, and then heat it to 800°C at 5°C / min and keep it for 12 hours to ensure that the raw materials are fully reacted and form a stable sodium vanadium phosphate-based composite material.

[0080] Post-treatment: The calcined product is naturally cooled to room temperature, and then ground and sieved through a 300-mesh sieve to obtain a magnesium / titanium / aluminum single-element doped sodium vanadium phosphate material with uniform particle size.

[0081] Comparative Example 3 (Double-element synergistic doping experiment)

[0082] This embodiment discloses a magnesium-titanium doped sodium vanadium phosphate, the preparation method of which is as follows:

[0083] Step 1, raw material mixing: according to the molar ratio of V:P:Na:Mg:Ti=1.9:3:3:0.05:0.05, weigh vanadium pentoxide V 2 O 5 、Ammonium dihydrogen phosphate NH 4 H 2 PO 4 、Sodium carbonate Na 2 CO 3 , magnesium oxide MgO, titanium dioxide TiO 2 and alumina Al 2 O 3 The raw materials were mixed in deionized water, 8 wt % of citric acid was added as a reducing agent, and the mixture was stirred at 80° C. to be uniform.

[0084] Step 2, precursor preparation: The solution is then spray dried at an inlet temperature of 200° C., an outlet temperature of 80° C., a flow rate of 20 rpm, and a pressure of 0.3 MPa to form a precursor of sodium vanadium phosphate.

[0085] Step 3, calcination treatment: the precursor powder is placed in a muffle furnace, and under nitrogen protection, the temperature is raised to 450°C at a rate of 5°C / min, and the temperature is maintained for 4 hours to ensure that the precursor is fully reduced, and then the temperature is raised to 800°C at a rate of 5°C / min and maintained for 12 hours to ensure that the raw materials are fully reacted and a stable sodium vanadium phosphate-based composite material is formed.

[0086] Step 4, post-treatment: the calcined product is naturally cooled to room temperature, and then ground and sieved through a 300-mesh sieve to obtain a (magnesium-titanium / magnesium-aluminum / titanium-aluminum) element-doped sodium vanadium phosphate material with uniform particle size.

[0087] Electrochemical performance tests were performed on the magnesium-titanium-aluminum doped sodium vanadium phosphate of Examples 1-3 and the sodium vanadium phosphate of Comparative Examples 1-3, including cyclic voltammetry test, charge-discharge test, rate performance test, etc., to evaluate their energy density, rate performance and cycle stability. At the same time, the structure and morphology of the material were characterized by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), etc.

[0088] The test results are as follows:

[0089] Cycle stability: The magnesium titanium aluminum doped sodium vanadium phosphate synthesized in Example 1 was assembled into a sodium ion battery positive electrode and subjected to a charge and discharge cycle test. At a rate of 0.1C, the initial discharge specific capacity was 112.24 mAh / g, and after 200 cycles, the capacity retention rate was 95%, showing excellent cycle stability.

[0090] Energy density: Compared with the undoped sodium vanadium phosphate material in comparative example 1, the energy density of the magnesium-titanium-aluminum-doped sodium vanadium phosphate synthesized in example 1 is increased by about 3.5% under the same test conditions, achieving a higher energy storage level.

[0091] Rate performance: Charge and discharge tests were carried out at different rates such as 1C, 2C, and 5C. The results showed that the magnesium-titanium-aluminum-doped sodium vanadium phosphate in Example 1 can still maintain good discharge performance at high rates, especially at a rate of 5C, the discharge specific capacity still remains above 90.77% of the initial value, showing excellent rate performance.

[0092] Figure 1 The XRD spectrum of magnesium-titanium-aluminum doped sodium vanadium phosphate in Example 1 shows its crystal structure characteristics. The crystal structure of magnesium-titanium-aluminum multi-element doped sodium vanadium phosphate material is shown, and the phase purity of the material is confirmed by comparing with the standard spectrum. It can be seen from the figure that the intensity and position of the relative diffraction peaks of sodium vanadium phosphate after magnesium-titanium-aluminum multi-element doping are basically consistent, which shows that the sample after multi-element doping does not change the phase purity of the material and maintains a good crystal structure.

[0093] Figure 2 This is a scanning electron microscope (SEM) image of magnesium-titanium-aluminum-doped sodium vanadium phosphate in Example 1. Figure 3 This is the second scanning electron microscope (SEM) image of magnesium-titanium-aluminum doped sodium vanadium phosphate in Example 1. The SEM shows that the magnesium-titanium-aluminum multi-element doped sodium vanadium phosphate has good sphericity after spraying. It can be seen that the particles of the doped sample are evenly distributed and have good particle size. Good consistency is conducive to the improvement of electrochemical performance, and the carbon coating effect of the doped sample is better, giving the material excellent powder resistivity.

[0094] Table 1 Charge and discharge cycle table

[0095]

[0096] Table 1 is a charge-discharge cycle table, which intuitively shows the capacity retention of the material during the cycle test.

[0097] According to the charge and discharge table, the multi-element doped magnesium titanium aluminum sodium vanadium phosphate has improved the initial efficiency and the capacity retention rate at a high rate compared to the undoped sodium vanadium phosphate. However, it is worth noting that as the content of multi-element doping continues to increase, the amount of active substances provided by vanadium redox is also gradually decreasing, which leads to a decrease in the discharge specific capacity provided by active sodium. Therefore, in the relevant experiments of multi-element doped sodium vanadium phosphate, attention should be paid to the content of doping elements to avoid the reduction of material specific capacity caused by excessive doping.

[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A magnesium-titanium-aluminum-doped sodium vanadium phosphate, characterized in that: Its general formula is Na3V 2-x Mg x / 4 Ti x / 4 Al x / 2 (PO4)3, where 0.1≤x≤0.

5.

2. A method for preparing the magnesium-titanium-aluminum-doped sodium vanadium phosphate according to claim 1, characterized in that: The following steps are involved: Step 1: Mix the raw materials According to the element ratio in the general formula, a vanadium source, a phosphorus source, a sodium source, a magnesium source, a titanium source and an aluminum source are weighed respectively, mixed in deionized water, and a reducing agent is added to obtain a mixed solution; Step 2: Precursor preparation The mixed solution is pre-treated by spray drying to prepare a precursor; Step 3: Calcination The precursor is placed in a high-temperature furnace and calcined under inert atmosphere protection: pre-sintered at 350-500°C for 2-4h, and then calcined at 800-950°C for 6-12h; Step 4: Post-processing After calcination, the magnesium-titanium-aluminum doped sodium vanadium phosphate is prepared by grinding and screening.

3. The method for preparing magnesium-titanium-aluminum-doped sodium vanadium phosphate according to claim 2, characterized in that: The vanadium source in step 1 is V2O5, NH4VPO4, V2O4, V2O3 and (NH4)2V6O 16 One or more of; and / or, the phosphorus source is one or more of NH4H2PO4, H3PO4, P2O5, (NH4)3PO4 and NH4VPO4; And / or, the sodium source is one or more of Na2CO3, NaCl, NaOH and NaHCO3; and / or, the magnesium source is one or more of MgO, Mg(OH)2, MgCO3 and Mg(NO3)2; And / or, the titanium source is one or more of TiO2, TiCl4 and H2TiO3; And / or, the aluminum source is one or more of Al2O3, Al(OH)3, AlCl3 and Al(NO3)3.

4. The method for preparing magnesium-titanium-aluminum-doped sodium vanadium phosphate according to claim 2, characterized in that: The solid content of the mixed solution in step 1 is 35-55%.

5. The method for preparing magnesium-titanium-aluminum-doped sodium vanadium phosphate according to claim 2, characterized in that: In step 1, the reducing agent is one or more of citric acid and ascorbic acid.

6. The method for preparing magnesium-titanium-aluminum-doped sodium vanadium phosphate according to claim 2, characterized in that: The amount of reducing agent added in step 1 is 5wt%-12wt%.

7. The method for preparing magnesium-titanium-aluminum-doped sodium vanadium phosphate according to claim 2, characterized in that: The spray drying conditions in step 2 are: spray inlet temperature 180°C-220°C, outlet temperature 80°C-120°C, flow rate 20-40rpm, and pressure 0.2-0.5Mpa.

8. The method for preparing magnesium-titanium-aluminum-doped sodium vanadium phosphate according to claim 2, characterized in that: The inert atmosphere in step 3 is one or more of nitrogen and argon.

9. The method for preparing magnesium-titanium-aluminum-doped sodium vanadium phosphate according to claim 2, characterized in that: The sieving in step 4 uses a 300-mesh sieve.

10. Use of the magnesium-titanium-aluminum-doped sodium vanadium phosphate according to claim 1 in the field of positive electrode materials for sodium ion batteries.